ANTI-RETROVIRAL DRUGS COMPLIANCE IN INTRAVENOUS AND NON INTRAVENOUS DRUG ABUSERS - Daud, Muhammad Yousuf; Qazi, Rizwan Aziz; Bashir, Naila (Journal of Ayub Medical College Abbottabad, 2014)
Background: Intravenous drug abuse is often associated with poor adherence to anti-retroviral drugs in HIV/AIDS. Very few studies in Pakistan have determined implications of intravenous drug abuse on anti-retroviral drug compliance in HIV/AIDS patients. The objectives of the study were to assess and compare the adherence to anti-retroviral drugs in intravenous drug users (IDUs) and non-intravenous drug users (NIDUs) and to determine various factors influencing the adherence to anti-retroviral (ARV) drugs in HIV positive IDUs in HIV treatment centre Pakistan Institute of Medical Sciences (PIMS), Islamabad. Methods: This descriptive observational study was carried out at HIV/AIDS treatment and care centre PIMS, Islamabad. A total of 162 HIV positive male (81 IDU and 81 NIDU) were enrolled in this study. They were followed over a period of five years from 2008-2012. ARV drug compliance and anti-tuberculosis treatment (ATT) outcome in IDUs and NIDUs were assessed using standard outcome parameters. Results: Among IDUs Hepatitis C was positive in 63 (77.77%) cases and negative in 18 (22.22%) cases. In NIDUs hepatitis C was positive in 5 (6.17%) and negative in 76 (93.82%) (p=0.000). In IDUs Pulmonary tuberculosis was present in 61 (75.30%) patients and in NIDUs it was present in 52 (64.19%) (p=0.171). Regarding ATT outcome, amongst IDUs 41 (50.61%) lost to follow up, 16 (19.75%) were compliant to treatment and 4 (4.93%) were transferred out. In NIDUs, 2 (2.46%) patients were lost to follow-up, 38 (46.91%) remained compliant to treatment and 6 (7.40%) were transferred out (p=0.000). Regarding end status of ARVs, in IDUs, 48 (59.25%) were lost to follow-up, 1 (1.23%) was defaulter, 16 (19.75%) were compliant to treatment, 8 (9.87%) were transferred out and 8 (9.87%) expired. In NIDUs, 73 (90.12%) were compliant to treatment, 5 (6.17%) expired, 2 (2.46%) were lost to follow-up. Conclusions: Due to various socioeconomic and clinical factors, compliance to ARVs in IDUs is poorer as compared to NIDUs. The factors recognized are illiteracy, poor socioeconomic status, unemployment and various comorbidities (Hepatitis B, C and Tuberculosis) which are more prevalent in IDUs. Keywords: HIV, Anti-retroviral drugs, Intravenous drug abusers, Non intravenous drug abusers